Disability-related inequalities in health and well-being are mediated by barriers to participation faced by people with disability. A causal mediation analysis. (December 2022) - Aitken, Zoe; Bishop, Glenda M; Disney, George; Emerson, Eric; Kavanagh, Anne M
Abstract: Large inequalities in health and well-being exist between people with and without disability, in part due to poor socio-economic circumstances, and potentially also related to societal factors including issues associated with accessibility and participation. To better understand the contribution of societal factors, we used a unique longitudinal survey of disability in Great Britain to quantify the extent to which barriers to participation contribute to poorer health and well-being. We used data from 2354 individuals who participated in three waves of the Life Opportunities Survey between 2009 and 2014 and compared five health and well-being outcomes (self-rated health, anxiousness, life satisfaction, life worth, happiness) between adults who acquired an impairment and those who remained disability-free. Causal mediation analysis was conducted to quantify how much of the effect of disability acquisition on each outcome was explained by barriers to participation in employment, economic life, transport, community, leisure and civic activities, social contact, and accessibility. People who recently acquired a disability had poorer health and well-being compared to people with no disability. Barriers to participation explained 15% of inequalities in self-rated health, 28% for anxiousness, 32% for life satisfaction, 37% for life worth, and 70% for happiness. A substantial proportion of the inequalities in health and well-being experienced by people with recently acquired disability were socially produced, driven by barriers to participation in different life domains. Furthermore, there was evidence that barriers to participation mediated the effect of well-being measured to a greater extent than the more clinically aligned measures, self-reported health and anxiousness. These findings highlight modifiable factors amenable to public health interventions that could lead to substantial improvements in health and well-being for people with disability. Highlights: Inequalities in health and well-being exist between people with and without disability. Existing evidence suggest inequalities are in part driven by socio-economic factors. The contribution of upstream societal barriers is not understood. Barriers to participation mediated a substantial proportion of the inequalities. Proportion mediated was larger for well-being compared to clinically aligned measures.